DESIGN OF COASTAL PROTECTION STRUCTURE BASED ON SEA WAVE PATTERN ANALYSIS USING CMS-WAVE MODEL AT KARYA TANI VILLAGE, LAMPUNG TIMUR DISTRICT, LAMPUNG - Banta - NIM : 15512013 , Siraragi
The beach is an area that is susceptible to the influence of the sea such as waves, currents, winds and tides, with one of the adverse effects of this is the decline of coastlines due to erosion caused by waves from the sea. Karya Tani Village Beach is a coastal area which experiences coastline decline every year. Economic activities around Karya Tani Village Beach which include fisheries and agriculture are threatened if no erosion problems are immediately addressed. To overcome this, it is necessary to plan coastal management program by using coastal protection structure. In this study, wave modeling was carried out with the CMS-Wave model of the SMS program. Modeling is divided into two stages, the first is wave modeling without using structures, and the second is wave modeling using a beach safety structure. By using the required data, the results of the modeling are the wave height profiles in the area that has been determined. From the results of the comparison of coastline from year to year taken from satellite images, it was concluded that Karya Tani Village Beach experienced significant erosion. Structural analysis is only done by looking at changes in wave patterns around the coastline caused by the construction of a coastal protection structure. The results of the two types of structures tested, only offshore breakwaters can change the wave pattern, while the groin does not function to change the wave height but to capture the movement of sediment. Because this study relies only on wave modeling, the chosen beach protection structure is offshore breakwaters